Exploring the regulatory mechanism of osteoporosis based on intestinal flora: A review. Issue 52 (30th December 2022) - Awuti, Kasimu; Wang, Xukai; Sha, Liquan; Leng, Xiangyang
Abstract : Osteoporosis is 1 of the common diseases of bone metabolism in clinic. With the aging of the population in China, osteoporosis is becoming more and more serious, and it has become 1 of the major public health problems. However, traditional therapies, such as calcium therapy and estrogen therapy, can cause serious adverse effects and damage to the body when ingested over a long period of time. Therefore, there is an urgent need to explore alternative therapies with less side effects in clinical practice. Intestinal flora is a hot topic of research in recent years. It has been studied in inflammatory bowel disease, diabetes, depression and so on. Recently, intestinal flora has received increasing attention in the pathways regulating bone metabolism. This paper contains a review of recent studies related to osteoporosis and gut flora in terms of its metabolites, immune, endocrine, and brain-gut axis pathways. The strong association between intestinal flora and bone metabolism suggests, to some extent, that intestinal flora can be a potential target for osteoporosis prevention and treatment, providing new ideas and therapies for the prevention and treatment of osteoporosis.